Preservation state of the sound and audiovisual documents in libraries of research institutes and centers of the National Autonomous University of México - Rodríguez Reséndiz, Perla Olivia (Revista General de Información y Documentación, 2019)
The libraries, like others memory institutions, have the challenge of preserving sound andaudiovisual documents recorded on analog carriers and born digital. This task is complex becauseuntil now the preservation of print materials has been privileged. However, it offers opportunities forlibraries that have not yet started this task. This paper presents the questionnaire results aboutpreservation state in libraries of research institutes and centers of science and humanities of theUNAM. It presents the situation and perspectives of analog and born digital sound and audiovisualcollections; the advances in the digitalization and the digital preservation tools used to guarantee thelong term permancen of these materials. To conclude, it stablishes a challenges to take inconsideration for the libraries.
Keywords: Analog preservation; Digital preservation; Sound archive; Audiovisual archive; Research institutes and centers